Nano-adjuvant based on silk fibroin for the delivery of recombinant hepatitis B surface antigen. (19th February 2021) - Rezaei, Fatemeh; Keshvari, Hamid; Shokrgozar, Mohammad Ali; Doroud, Delaram; Gholami, Elham; Khabiri, Alireza; Farokhi, Mehdi
Abstract : Silk fibroin nanoparticles as a natural polymer can be used as a nano-adjuvant for delivering the recombinant hepatitis B surface antigen. Abstract : Nanotechnology has a vital role in vaccine development. Nano-adjuvants, as robust delivery systems, could stimulate immune responses. Using nanoparticles (NPs) in vaccine formulations enhances the target delivery, immunogenicity, and stability of the antigens. Herein, silk fibroin nanoparticles (SFNPs) were used as a nano-adjuvant for delivering recombinant hepatitis B surface antigen (HBsAg). HBsAg was loaded physically and chemically on the surface of SFNPs. The HBsAg-loaded SFNPs had a spherical morphology. The in vitro release studies showed that HBsAg had a continuous and slow release from SFNPs during 56 days. During this time, ∼45.6% and 34.1% HBsAg was released from physical-SFNPs and chemical-SFNPs, respectively. HBsAg-loaded SFNPs were also stable for six months with slight changes in the size, surface charge, and morphology. The results of circular dichroism (CD) and fluorescence spectroscopy indicated that the released HBsAg preserved the native secondary and tertiary structures. The quantitative cellular uptake study also showed that physical-SFNPs were taken up more into J774A.1 macrophage cells than chemical-SFNPs. After 28 and 56 days post-injection, the immunogenicity studies showed that the specific total IgG, IgG1, and IgG2a levels against HBsAg were significantly higher in the physically loaded group than in the chemically loaded group and commercial hepatitis B vaccine. IgG2a levels were detected only in mice immunized with physical-SFNPs. However, the low levels of IL-4 and IFN-γ were produced in all vaccinated groups and differences in mean values were not significant compared with control groups. Results indicated an improvement in the levels of anti-HBsAg IgG in mice immunized with the physical-SFNPs group compared to other groups.